2020
DOI: 10.37624/ijert/13.7.2020.1786-1794
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Computer-Assisted Instruction on Mathematics and Physics Students’ Achievement: Implication for Industrial Technical Education

Abstract: Twenty-first century classrooms have come with a lot of changes in the instructional delivery at various levels of education. However, most teachers in Nigerian still adopt the traditional method of instruction not minding the demands of the twenty-first century classrooms. As a result of this, there is dearth of empirical evidence on the impact of computerassisted instruction on the students' achievement in mathematics and physics. This study, therefore, evaluated the impact of computer-assisted instruction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…However, during the pandemic, the situation is worse due to lack of or slow communication between teachers and learners. Thus, physics teachers opted for computer simulations that proved effective in improving physics achievement during in-person classes (Bayrak 2008;Constante and Agsalud 2019) and during distance classes (Azizah et al 2022;Onah et al 2020;Yusuf and Widyaningsih 2020) similar to the findings of the current study.…”
Section: Discussionsupporting
confidence: 72%
“…However, during the pandemic, the situation is worse due to lack of or slow communication between teachers and learners. Thus, physics teachers opted for computer simulations that proved effective in improving physics achievement during in-person classes (Bayrak 2008;Constante and Agsalud 2019) and during distance classes (Azizah et al 2022;Onah et al 2020;Yusuf and Widyaningsih 2020) similar to the findings of the current study.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, some studies claim that CAI is effective in improving students' achievement as compared to traditional lecturing [5][6]. Onah et al [7] used the Mathematics Achievement Test (MAT) and Physics Achievement Test (PAT) and found that CAI significantly improved mathematics and physics students' achievement. Kaye and Ehren [8] reported that key factors that should be considered when designing CAI interventions include the operating environment, stakeholder engagement, infrastructure, technological trust, CAI tool design, content curation/creation, student engagement, classroom integration, teacher capacity, and student capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In the global context, studies (Agboeze et al, 2020;Ugwuanyi, Okeke & Njeze, 2020;Benson et al, 2020;Inyama, Nwagbo & Ugwuanyi, 2020;Ugwuanyi et al, 2019a;Ugwuanyi et al, 2019b;Ugwuanyi, Okeke, & Ageda, 2020;Onah et al, 2020;Njoku et al, 2020;) have noted the decline in the achievement of learners in science subjects including basic science. This abysmal performance of learners in basic science could be attributed to the non-implementation of the inquirybased approach in some countries (Inyama, Nwagbo & Ugwuanyi, 2020;Benson et al, 2020).…”
Section: Background and Statement Of The Problemmentioning
confidence: 99%